2020
DOI: 10.18502/ijph.v48i6.2928
|View full text |Cite
|
Sign up to set email alerts
|

Family Medicine Program in Iran: SWOT Analysis and TOWS Matrix Model

Abstract: Abstract Background: We aimed to determine strength, weakness, opportunities and threats analysis and intended to present strengths, weaknesses, opportunities and threats matrix model for appropriate implementation of Family medicine program in Iran. Methods: This was a descriptive-analytical and cross-sectional study. All attending physicians in 30 health care centers of Tehran University of Medical Sciences, Tehran, Iran were asked to present and prioritized their views about strengths, weaknesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Al-khathami, also argued the importance of quality health care at the primary care level for patient satisfaction and better health outcomes [ 16 ]. The SWOT Analysis of Family medicine programme in Iran identified that implementation of the family medicine program is essential to improve and strengthen primary health care in a developing country like Iran in a very cost-effective way [ 19 ]. The Besrour papers on developing family practice also reported that the implementation of family medicine practice is the key to overcome the challenges in developing countries who are having the issue of brain drain while the community is facing enormous challenges regarding health care [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al-khathami, also argued the importance of quality health care at the primary care level for patient satisfaction and better health outcomes [ 16 ]. The SWOT Analysis of Family medicine programme in Iran identified that implementation of the family medicine program is essential to improve and strengthen primary health care in a developing country like Iran in a very cost-effective way [ 19 ]. The Besrour papers on developing family practice also reported that the implementation of family medicine practice is the key to overcome the challenges in developing countries who are having the issue of brain drain while the community is facing enormous challenges regarding health care [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two decades ago, Iran introduced the FM program as part of its primary healthcare network reforms 15 . FM focuses on providing PHC services, including preventive care, diagnosis, treatment of common diseases, and management of chronic diseases, and is funded primarily through public sources in Iran 16 . The structure of FM is organized in the form of primary care units, rural healthcare centers and urban healthcare centers, and the Ministry of Health and Medical Education (MoHME) sets policies and regulations for the healthcare and FM system.…”
Section: Introductionmentioning
confidence: 99%
“… 15 FM focuses on providing PHC services, including preventive care, diagnosis, treatment of common diseases, and management of chronic diseases, and is funded primarily through public sources in Iran. 16 The structure of FM is organized in the form of primary care units, rural healthcare centers and urban healthcare centers, and the Ministry of Health and Medical Education (MoHME) sets policies and regulations for the healthcare and FM system. MoHME and its affiliated organizations monitor quality through inspections, performance indicators, and accreditation.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lee and Allen consisting of 149 RNs from Ontario Canada, with over 70 percent working in a general hospital, found that job affects (feelings about work) were associated more strongly than were job cognitions (thoughts about work such as fairness, recognition) with OCBs directed at individuals, whereas job cognitions correlated more strongly than did job affects with OCBs directed at the organization (Lee & Allen, 2002). A cross-sectional, descriptive and analytical study by Dargahi, Alirezaie, and Shaham (2012) conducted among 510 nurses working in teaching hospitals in Tehran, Iran, confirmed the existence of OCBs among nurses with frequent demonstration of sportsmanship, civil virtue, conscientiousness, and altruism behaviors (Dargahi, Alirezaie, & Shaham, 2012).…”
mentioning
confidence: 99%
“…This paper describes a psychometrics exercise that was conducted as a precursor to a larger study which focuses on work attitudes and work-related behaviours shown to relate to work motivation in the health services literature (Chu et al, 2005;Dargahi et al, 2012;Lee & Allen, 2002) and in the organization studies literature (Greenberg, 2009;Lavelle, 2007;Lavelle et al, 2009;Mathieu & Zajac, 1990;Morin et al, 2011;Rhoades, Eisenberger, & Armeli, 2001;Rupp & Cropanzano, 2002;Solinger, van Olffen, & Roe, 2008). Specifically, the larger study examines the relationship between the work attitude affective commitment and OCBs.…”
mentioning
confidence: 99%